A modular torso phantom featuring a pneumatic stepper and flow for MR sequence development - Körner, Tito; Wampl, Stefan; Kiss, Lorenz; Oberoi, Gunpreet; Unger, Ewald; Birkfellner, Wolfgang; Schmid, Albrecht I. (Frontiers in Physics, 2024)
Phantoms mimicking tissue motion have become a valuable tool for quality control in various fields of medical physics including lung phantoms for image-guided radiotherapy and functional imaging in nuclear medicine or magnetic resonance imaging (MRI) in the body. In MRI, precise kinematic models are more difficult to realize owing to the requirements of MR-compatibility. Pneumatic stepper motors built entirely of non-conducting materials can be safely used in an MR environment, with pressurized air supply and switching residing outside the magnet room. In this research, a torso phantom was built adopting a 3D-printed linear stepper drive for use with high-field MR scanners. It was possible to simulate respiratory motion of a 3D-printed left ventricle phantom using the stepper. Precise and accurate motion for a time of 15 minutes over a range of 8 cm were achieved with speeds up to 5.5 mm/s when the stepper was loaded with the left ventricle phantom. It was shown that the motor is an effective tool for quality control in multi-modal medical imaging.